Kandungan Senyawa Aktif Metabolit Sekunder dalam Biolarvasida - Annasya, Benazhir Saninah; Mutiara, Hanna; Marcellia, Selvi (CV. Jasa Sukses Abadi, 2025)
Larvicide is a compound that can be toxic, inhibit growth and development, affect behavior, affect hormones, inhibit feeding, and act as a larval killer. Larvicide is divided into two types, namely chemical larvicide and biolarvicide. Chemical larvicide is the larvicide most widely used by the community because it has a large substance strength. However, the use of chemical larvicide can cause damage, especially insects become resistant to drugs, in addition to causing environmental pollution because synthetic larvicide is difficult to decompose and causes poisoning in humans. The use of chemical larvicide can cause damage, especially insects become resistant to drugs, in addition to causing environmental pollution because synthetic larvicide is difficult to decompose and causes poisoning in humans. Therefore, a substitute for chemical larvicide in the form of biolarvicide is needed. Biolarvicide can act as a larval killer, attractant, antifertility agent (sterilization tool), biocide, and other forms that minimally cause drug resistance in insects. Biolarvicide comes from plant materials containing active compounds of secondary metabolites such as essential oils, saponins, steroids, terpenoids, tannins, alkaloids, flavonoids, and phenolics that can kill mosquito larvae and are obtained by extraction. This article provides a broader explanation of the content of secondary metabolite compounds in biolarvicide so that it can be more effectively used as a larvicide from natural materials. The contents of the article were obtained through searches of several national and international journals through the search keywords: Biolarvicide, secondary metabolites, and active compounds.